ANALISIS PENGADAAN BAHAN BAKU, KEUNTUNGAN, SALURAN PEMASARAN, DAN JASA LAYANGAN PENDUKUNG AGROINDUSTRI KERIPIK SINGKONG DIKELURAHAN GANJAR ASRIKECAMATANMETRO BARATKOTA METRO - Yuli Dwi Sulistioningrum; Ktut Murniati; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This research aims to: analyze the procurement of raw materials, profits, marketing channels,and the role of cassava chip agroindustry support services in Ganjar Asri Village. This study used a census method on five agroindustry cassava chips in Ganjar Asri Village West Metro Subdistrict Metro District. The determination of the location was done deliberately with the consideration that Ganjar Asri Village was a center of cassava chipsagroindustry actively produce and have the potential to be developed. The respondents were the owners of five agroindustries. The results showed that: there are two components of raw material procurement that were in accordance with expectations carried out by the five cassava chips agroindustries, namely quantity and type, while the other five components have not been in accordance with expectations, namely time, place, quality, and price. The highest profit is in Matahari Agroindustry and amounted to IDR 1,412,017.80 in one production. All agroindustries have benefits, so they were worthy of effort and development. Support services that helped the process of cassava chip agroindustry activities are financial institutions, transportation facilities, and communication information technology.Key words: advantage, agroindustry, cassava chips.